1998
DOI: 10.1002/(sici)1096-8628(19980401)76:4<337::aid-ajmg9>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Identification of heterozygotic carriers of 21-hydroxylase deficiency: Sensitivity of ACTH stimulation tests

Abstract: Congenital adrenal hyperplasia due to 21-hydroxylase deficiency is a common autosomal-recessive disorder. To ascertain carrier status, adrenocorticotropin (ACTH) stimulation tests are often used. To determine the sensitivity of ACTH stimulation to detect heterozygotes and to correlate stimulated 17-hydroxyprogesterone responses with molecular genotype, we compared molecular genetic analysis of the 21-hydroxylase (CYP21) gene with 17-hydroxyprogesterone responses at 30 min in 51 individuals. Molecular genotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 28 publications
(28 reference statements)
1
16
1
3
Order By: Relevance
“…This is in agreement with observations that heterozigosity for CYP21 mutations may result in mild abnormalities of androgen biosynthesis reflected by higher mean free testosterone (13,30) or by higher mean DHEAS concentrations (10). Our results suggest that, in contrast with findings in patients with NC-CAH, among hyperandrogenic women, basal or ACTHstimulated 17-OHP concentrations are not a good indicator of the carrier status for inherited defects of CYP21, as observed also by other investigators (13,31,32) who defined the carrier status by molecular analysis of CYP21 gene, the most accurate method to define carriers for inherited defects of CYP21 (10). Older studies reported that the majority of heterozygotes for 21-hydroxylase deficiency can be detected by measuring the 17-OHP concentration 60 min after ACTH stimulation; however, the diagnosis of 21-hydroxylase deficiency was based on HLA genotyping (33 It remains unclear what was the cause of borderline elevations in ACTH-stimulated 17-OHP concentrations in nine of 12 hyperandrogenic patients (75%), in whom even extensive sequencing of the CYP21 gene and its proximal promoter region revealed no mutations.…”
Section: Discussioncontrasting
confidence: 83%
“…This is in agreement with observations that heterozigosity for CYP21 mutations may result in mild abnormalities of androgen biosynthesis reflected by higher mean free testosterone (13,30) or by higher mean DHEAS concentrations (10). Our results suggest that, in contrast with findings in patients with NC-CAH, among hyperandrogenic women, basal or ACTHstimulated 17-OHP concentrations are not a good indicator of the carrier status for inherited defects of CYP21, as observed also by other investigators (13,31,32) who defined the carrier status by molecular analysis of CYP21 gene, the most accurate method to define carriers for inherited defects of CYP21 (10). Older studies reported that the majority of heterozygotes for 21-hydroxylase deficiency can be detected by measuring the 17-OHP concentration 60 min after ACTH stimulation; however, the diagnosis of 21-hydroxylase deficiency was based on HLA genotyping (33 It remains unclear what was the cause of borderline elevations in ACTH-stimulated 17-OHP concentrations in nine of 12 hyperandrogenic patients (75%), in whom even extensive sequencing of the CYP21 gene and its proximal promoter region revealed no mutations.…”
Section: Discussioncontrasting
confidence: 83%
“…At the hormone level, heterozygotes have normal or only slightly elevated basal plasma levels of 17-hydroxyprogesterone (17OHP) (3). Following corticotrophin (ACTH) injection, heterozygotes usually show an increased rise of 17OHP compared with controls, but it is not possible to identify heterozygosity based on stimulated 17OHP alone (11,12,13,14). A different approach to detect heterozygotes is the calculation of substrate-to-product ratios.…”
Section: Introductionmentioning
confidence: 99%
“…33 Whereas an ACTH-stimulated17-OHP concentration less than 400 mg/dl is reassuring that the person is not a carrier, molecular genetic testing may be needed to completely exclude carrier status. 86 …”
Section: Diagnosismentioning
confidence: 99%